Strategies to improve nurses working conditions in selected public clinics of the Limpopo Province, South Africa - Motsepe, Thembi Julia (My University, 2021)
In this study, the working conditions of nurses in the public clinics are assessed as the nurses are not satisfied with their working conditions. The dissatisfaction on nurses working conditions by nurses was identified and observed by the researcher at certain clinics in the Sekhukhune District. Strategies are suggested to improve nurses’ working conditions in the selected public clinics of the Limpopo Province, South Africa. The study aims to develop strategies to improve nurses’ working conditions in selected public clinics of Limpopo Province, South Africa. A qualitative exploratory and descriptive research approach, using a phenomenological design has been used. Data were collected from professional nurses from the selected public clinics, using semi-structured interviews. Data were audiotaped and field notes were taken. The eight Steps of Tesch’s inductive, descriptive open coding technique, described by Creswell was used, followed by independent coding. Purposive sampling recruited 20 professional nurses from seven selected clinics in the Limpopo Province. The Turfloop Research Ethics Committee gave ethical clearance. The Department of Health gave permission for the study to be conducted in the selected clinics. Ethical considerations and measures to ensure trustworthiness have been observed. The results show that nurses’ working conditions are affected by the shortage of human and material resources, poor health clinic structures, unacceptable duty schedules, large numbers of clients which to lead to nurses’ burnout. In addition, there is the challenge of the different roles played by nurses, which impede the provision of quality patients’ care. The nurses suggested that the Department of Health should be transparent regarding any information regarding issues of the health system. Furthermore, strategies to improve patients’ awareness regarding the nurses’ working conditions have been developed from the themes that emerge from this study. The findings of the study cannot be generalized to other clinics of the Limpopo province and of other provinces.
Thesis (M. A.(Nursing Science)) -- University of Limpopo, 2021
Keywords: Strategies; Working conditions; Nurses -- Employment; Work environment; Nurses -- South Africa -- Limpopo; Employee health promotion